Ask Drum Tom
MAKE MONEY ANSWERING QUESTIONS
ABOUT
FIND THE ANSWERS
F(x)=x3−2x+6 g(x)=2x3+3x2−4x+2 Find (f−g)(x).?
Tweet
Answer this question
Do you know the correct answer? Make money answering questions! Join now.
F(x)=x3−2x+6 g(x)=2x3+3x2−4x+2 Find (f−g)(x).?
Answer for question:
Your name:
Answers
recent questions
BANKKING in ny ssi turn into a bussines
ED hortice .all circle for bussiness
what are five body system that monitor homeostasis
9.647×107=
what is the slope of the line passing through (-2, 5) and (3,-4)
Anonymous82085
Login to your account
Create new account
Discover Questions
What are gradually changes on earth?
Given f(x)=2x+1/3 find f^-1(x)?
What is 5/6+5/7*1/5?
Six less than 9?
How much resistance and tolerance does a resistor that has the color bands red, violet, orange, gold have? Show your calculation.?